Differential response of the microbiome of pocillopora acuta to reciprocal transplantation within singapore - Deignan, Lindsey Kane (2022)
As corals continue to decline globally, particularly due to climate change, it is vital to understand the extent to which their microbiome may confer an adaptive resilience against environmental stress. Corals that survive on the urban reefs of Singapore are ideal candidates to study the association of scleractinians with their microbiome, which in turn can inform reef conservation and management. In this study, we monitored differences in the microbiome of Pocillopora acuta colonies reciprocally transplanted between two reefs, Raffles and Kusu, within the Port of Singapore, where corals face intense anthropogenic impacts. Pocillopora acuta had previously been shown to host distinct microbial communities between these two reefs. Amplicon sequencing (16S rRNA) was used to assess the coral microbiomes at 1, 2, 4, and 10 days post-transplantation. Coral microbiomes responded rapidly to transplantation, becoming similar to those of the local corals at the destination reef within one day at Raffles and within two days at Kusu. Elevated nitrate concentrations were detected at Raffles for the duration of the study, potentially influencing the microbiome's response to transplantation. The persistence of corals within the port of Singapore highlights the ability of corals to adapt to stressful environments. Further, coral resilience appears to coincide with a dynamic microbiome which can undergo shifts in composition without succumbing to dysbiosis.